Library therapeutic landscape quality and satisfaction - Husaini, Haslinda; Noordin, Siti Arpah; Muhamad Shuhidan, Shamila (Universiti Teknologi MARA, Kedah, 2017)
Emerging practices are changing the landscape of traditional therapies. The idea of therapeutic landscape used to show the relationship between place and improvements in mental health. In the context of a library, the purpose is to make sure that the quality of the library products, facilities and services is up to the expectation that the users perceived. The surrounding environment of an organization or institution may influence the customers/users’ therapeutic satisfaction, yet in a library setting, studies on the therapeutic landscape quality is still lacking. The incorporation of therapeutic landscape in the library, especially the environmental elements may enhance the library users’ therapeutic Satisfaction. With the therapeutic landscape dimension, library users’ satisfaction in term of therapeutic elements may be measured. The research evaluates user’s experience using three constructs which include the following elements: naturaland built environments, social environment and spiritual environment of the library. Further, the paper reported on the result of proposed research, thinking about the library’s role as an environment and not as service provider. The assessment of perceived library therapeutic landscape quality may provide some insights on how users rate the library therapeutic landscape quality of public libraries. Thus, the findings can be used as a guide for library management to improve the crucial quality attributes and enhance the quality of the therapeutic landscape of the library.